State of the Arctic Marine Biodiversity Report: Key Findings and Advice for Monitoring - Conservation of Arctic Flora and Fauna (CAFF) (Conservation of Arctic Flora and Fauna, 2017)
By compiling available information, this report provides an important first step to identify knowledge gaps in circumpolar biodiversity monitoring efforts. Current biodiversity monitoring is not sufficient to describe the status and trends for may of th FECs. Snapshots of the state of knowledge and trends for FEC are provided. Advice for monitoring includes better coordination, standardization of methods, improved consideration of traditional and Local Knowledge (TLK), and attention to filling key gaps. The State of the Arctic Marine Biodiversity Report (SAMBR), is a product of the Circumpolar Biodiversity Monitoring Program (CMBP) of the Arctic Council's Conservation of Arctic Flora and Fauna (CAFF) Working Group. The SAMBR is a synthesis of the state of knowledge about biodiversity in Arctic marine ecosystems, detectable changes, and important gaps in our ability to assess state and trends in biodiversity across six Focal Ecosystem Components (FECs): sea ice biota, plankton, benthos, marine fishes, seabirds and marine mammals.